Exploring the role of community level social capital in the context of climate-smart agriculture: Field notes from Cauca, Colombia - Martinez Baron, Deissy (2022)
This report presents findings from focus group discussions (FGDs) conducted in Cauca, Colombia, focusing on the role of community-level social capital in Climate-Smart Agriculture (CSA). The research explores how social capital, defined by the networks, relationships, and trust within the community, influences the adoption and scaling of CSA practices. Social capital is examined through bonding, bridging, and linking dimensions, assessing how local networks facilitate knowledge exchange, decision-making, and resilience in response to climate variability.